ELECTROPHYSIOLOGICAL CHANGES IN LATENCY IN DIABETIC RETINOPATHY: AN OBSERVATIONAL STUDY - Vijay More, Amruta; Ghodake, Aparna; Shah, Chintan; Chhabra, Aishwarya; Gosai, Jignesh (International Journal of Clinical and Biomedical Research, 2017)
Purpose: Multifocal ERG is a useful indicator of diabetic retinopathy. The significant delay in local responses provides a chance for the detection and understanding of the various stages of diabetic retinopathy. Materials and Methods: This is a cross sectional study conducted in ERG clinic at M & J Western regional institute of ophthalmology, Ahmedabad from January 2013 to September 2015 who were more than 35yrs of age. Results: In our study, we studied 45 eyes of diabetic patients and 20 eyes of normal subjects. In our study the mean values of the various parameters was calculated in the control group with N1, P1 and N2 latency being 14.09ms. 29,76ms and 45.55ms respectively. The N1, P1 and N2 amplitude was found to be 31.52nV, 73.61nV and 90.38nV respectively. The maximum delay in N1, P1 and N2 latency was seen to be 3.24ms, 7.11ms and 8.40ms respectively from the normal value. We also found a decrease in amplitude of the ERG waveform with N1, P1 and N2 amplitude being 20.98nV, 61.48nV and 76.4nV respectively from the normal value. Also it is helpful in cases with clinically significant macular edema where responses are remarkably delayed suggesting local retinal dysfunction and macular pathology. It provides us information regarding the condition of the macula and some ideas about the extent of ischemia affecting this area. Conclusion: In conclusion, we can say that the delayed responses obtained indicate abnormal retinal function corresponding to local discrete retinal lesions. It provides a very sensitive and objective assessment of the local retinal condition in various stages of diabetic retinopathy. KEYWORDS: Diabetes mellitus; Diabetic retinopathy; Multifocal electroretinogram.